The role of palmitic acid on endoplasmic reticulum stress: implication In cancer cell survival - Soumya V V (Amala Cancer Research Center, Trissur, 2025)
Palmitic acid, a major saturated fatty acid found in palm oil and other dietary sources, plays a crucial role in cellular metabolism, particularly in lipid metabolism, oxidative stress, and endoplasmic reticulum (ER) stress. When excessive palmitic acid induces ER stress, where protein-folding demands surpass the capacity of ER, it may disrupt cellular balance and potentially lead to cell dysfunction or death. Considering the evidence linking ER stress to various pathological conditions, understanding the mechanistic impact of palmitic acid on ER stress and cellular fate is crucial. This study investigates the molecular pathways through which palmitic acid influences ER stress and its downstream effects, providing insights into its potential role in disease progression and metabolic disorders. Additionally, UPR signalling in metastasised tumour-bearing mice administered with palm oil will be analysed. In vitro experiments revealed a decline in cell viability dose-dependently across all cell lines. Notably, IEC6 cells exhibited greater tolerance (IC50: 342 μM) than cancer cells, with IC50 values of 180 μM for HCT116 and 168 μM for CT26. Morphological alterations, including cell structure disruption, were minimal at lower concentrations but became significant at higher doses. Both normal and cancer cells were found to accumulate neutral lipids, indicating the involvement of fatty acid transport proteins. Notably, both normal cells and cancer cells showed significant lipid accumulation even at lower concentrations and retained the ability to form colonies, indicating resilience under metabolic stress. However, at higher concentrations, palmitic acid disrupted lipid metabolism and compromised antioxidant defences, ultimately leading to cell death. Excess lipid accumulation in cells led to increased ROS and the accumulation of misfolded proteins at both low and high doses. The upregulation of ER stress marker genes Bip, Chop, and Atf6 further indicated ER stress and misfolded protein accumulation. These findings suggest that palmitic acid disrupts protein folding mechanisms and ER functionality at higher concentrations, leading to cellular dysfunction, while cells can withstand the stress at lower concentrations, indicating that oxidative stress-associated metabolic stresses play a crucial role in ER stress in pathological and physiological contexts. The ER stress-associated UPR pathways, particularly PERK/ATF4, IRE1/XBP1, and ATF6, play a crucial role in cell survival under stress. Palmitic acid is found to activate the PERK pathway and enhance the antioxidant enzymes like superoxide dismutase ix(SOD), catalase (CAT) etc, at sub-lethal doses. However, the activity declined to its toxic level. The glutathione-based antioxidants were stable at lower doses but dropped significantly at toxic concentrations, emphasising their role in detoxifying palmitic acid metabolites. Lipid peroxidation level was also increased by palmitic acid, diminishing antioxidant defences, compromising membrane integrity, and heightening oxidative stress at higher doses. Stress-responsive factors Nrf2, Nqo1and Ho-1, key antioxidant defence and autophagy regulators, showed variable expression. The cancer cells, HCT116 and CT26, displayed Nrf2 upregulation compared to normal IEC6 cells. This highlights the adaptive responses of cancer cells under toxic stress to maintain homeostasis. This may lead to cell survival mechanisms. Palmitic acid treatment resulted in the formation of acidic vacuoles, indicating an autophagic response. Further, acidic vacuoles led to autophagy, as evidenced by MDC staining. The expression of autophagy-related genes Beclin 1 and Lc3b1, along with UPR markers Ire1 and Xbp1, was upregulated particularly in cancer cells, suggesting that palmitic acid enhances cellular resistance to stress through the activation of both autophagy and ER stress pathways. This link between autophagy and ER stress is critical, as autophagy alleviates ER stress by degrading damaged cellular components, while the UPR regulates autophagic flux. This interaction may promote cell survival and progression in colon cancer, indicating potential therapeutic strategies for targeting these pathways to inhibit cancer survival mechanisms. In vivo studies were conducted using a palm oil-rich diet to analyse the impact of prolonged intake of heat-treated palm oil (HPO), which is high in palmitic acid, on colon cancer metastasis. Using gas chromatography-mass spectrometry/mass spectrometry (GC-MS/MS) analysis determined a palmitic acid concentration of 367 mg/mL in HPO. Over four months, mice received 200 μl of HPO, corresponding to 73.4 mg of palmitic acid per mouse. HPO consumption caused oxidative stress and reduced antioxidant levels in the small intestine, leading to increased lipid peroxidation. This oxidative stress was less pronounced in the large intestine due to its limited lipid absorption capacity. Histopathological analysis revealed significant alterations in goblet cell morphology, inflammation, and ER stress development in the intestinal tissues. Prolonged HPO intake led to the upregulation of ER stress markers such as BIP, CHOP, and ATF6 and the activation of different UPR pathways, with the PERK/ATF4 xpathway being more active in the small intestine and the IRE1/XBP1 pathway in the large intestine. The study investigated the effect of HPO on CT26 cell-induced colon cancer pulmonary metastasis. Oral administration of HPO in mice with CT26 inoculated cancer led to metastasis along with inflammatory cell infiltration. Consistent with previous findings, HPO promoted metastasis through the TLR4/TRIF-Peli1-pNF-κB pathway, while CD36 blockade effectively inhibited this process. HPO treatment exhibited significant body weight loss, glucose intolerance, and systemic inflammation, accompanied by elevated counts of white blood cells, monocytes, neutrophils, lymphocytes, and platelets, suggesting immune modulation. Additionally, HPO influenced lipid metabolism in cancer progression, as evidenced by increased serum cholesterol, triglycerides, and LDL levels. Elevated AST and ALT levels indicated liver dysfunction, while increased lung hydroxyproline and collagen deposition suggested a potential link between HPO exposure and pulmonary fibrosis. The colon cancer pulmonary metastasis further impacted inflammatory responses, oxidative stress, ER stress, and associated signalling pathways by HPO. Palmitic acid- induced inflammation in lung tissues, characterised by elevated levels of IL-6 and TNF- α, creates a microenvironment favourable for metastatic spread. Increased immune cell infiltration and invasion further supported the role of HPO-induced inflammation in facilitating cancer cell aggressiveness. Chronic HPO intake disrupted redox homeostasis in lung tissues, leading to oxidative damage exacerbated by alterations in antioxidant enzymes. Significant changes in glutathione-related enzymes without corresponding adjustments in SOD and CAT underscored a dysregulated antioxidant defence system, potentiating oxidative stress and inflammation. HPO-induced ER stress, evidenced by the upregulation of ER stress markers like Bip, Chop, Atf6, and the activation of Perk/Atf4 and Ire1/Xbp1 signalling pathways, contributed to a pro- tumorigenic microenvironment favouring cancer metastasis. In conclusion, palmitic acid-induced oxidative and ER stresses disrupt cellular homeostasis, triggering UPR pathways and impairing antioxidant defences. Cancer cells exhibit metabolic resistance, with increased lipid accumulation and stress adaptation mechanisms. In vivo, prolonged HPO intake led to systemic inflammation, immune modulation, and liver dysfunction. HPO-driven ER stress and inflammation in lung tissues, characterised by IL-6 and TNF-α elevation, created a tumour-promoting ximicroenvironment, facilitating metastatic progression. The dysregulation of antioxidant defence systems further exacerbated oxidative damage. CD36 blockade mitigated HPO-induced metastasis, underscoring the potential of targeting fatty acid metabolism in cancer therapy. These findings provide mechanistic insights into the interplay between lipid metabolism, ER stress, and tumour progression, emphasising the need for dietary interventions and therapeutic strategies to counteract palmitic acid-driven cancer aggressiveness.
Keywords: Palmitic Acid ER Stress Oxidative Stress Autophagy